Dressed Coolie Woman. All Gold. Trinidad B.W.I. - (:unkn) unknown (My University, 2009)
East Indian woman in traditional wear, adorned with gold jewellery.
Colour: Coloured; Style: Portrait Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Women, East Indian--Trinidad and Tobago; Jewelry--India; Ethnic costume--India; Clothing and dress--Trinidad and Tobago